2019
DOI: 10.1021/acsomega.8b02757
|View full text |Cite
|
Sign up to set email alerts
|

Role of Generation on Successful DNA Delivery of PAMAM–(Guanidino)Neomycin Conjugates

Abstract: The decoration of polyamidoamine (PAMAM) dendrimers with some functional moieties holds promises for improving the gene-delivery behavior of the resulting polyplexes. Herein, we reported the synthesis and the development of nonviral gene vectors built on an array of PAMAMs, spanning generation 2 (G2), G4, and G7, specifically tethered with multivalent neomycin (Neo) or guanidinoneomycin (GNeo). Following a thorough chemical characterization by means of NMR and MALDI analyses, the ability of PAMAM−(G)Neo conjug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 63 publications
0
39
0
Order By: Relevance
“…Some authors have indeed reported that the transfection efficiency of bPEI in vitro increased with increasing the M W of the CP (in the range from ≈1.8 to ≈70 kDa) [62,114], while others have highlighted that the lower the M W of the branched polymer (≈12 kDa), the greater the effectiveness [115]. Further, we and some others have pointed out the different pDNA complexation ability of lPEI and bPEI and have found that, irrespective of the M W of the CP taken into account, lPEIs complex best at N/P 5, while bPEIs at N/P 3 [57,62,64,116,117]. This different behavior may be ascribed to the different structures of the PEI isomers: of note, lPEI possesses only secondary amines, while bPEI has primary, secondary, and tertiary amines depending on the polymerization degree [118].…”
Section: Cationic Polymers (Cps)mentioning
confidence: 53%
See 3 more Smart Citations
“…Some authors have indeed reported that the transfection efficiency of bPEI in vitro increased with increasing the M W of the CP (in the range from ≈1.8 to ≈70 kDa) [62,114], while others have highlighted that the lower the M W of the branched polymer (≈12 kDa), the greater the effectiveness [115]. Further, we and some others have pointed out the different pDNA complexation ability of lPEI and bPEI and have found that, irrespective of the M W of the CP taken into account, lPEIs complex best at N/P 5, while bPEIs at N/P 3 [57,62,64,116,117]. This different behavior may be ascribed to the different structures of the PEI isomers: of note, lPEI possesses only secondary amines, while bPEI has primary, secondary, and tertiary amines depending on the polymerization degree [118].…”
Section: Cationic Polymers (Cps)mentioning
confidence: 53%
“…Because they are relatively safe, display easily tunable physico-chemical properties, can be produced in large quantities with high reproducibility and affordable costs, and show unlimited ferrying capacity [53][54][55], non-viral vectors are nowadays at the forefront of gene delivery [1]. The two major approaches to non-viral gene delivery involve the combination of NAs with transfection molecules, that is, cationic lipids (CLs; e.g., DOTAP, DOTMA) [56][57][58][59][60][61] in different forms, and cationic polymers (CPs; e.g., poly-L-lysines, polyethyleneimines (PEIs), poly(amidoamine)s, chitosans) [62][63][64][65][66][67]. The beauty of this approach lies in its simplicity, yet in its effectiveness.…”
Section: Nucleic Acid Description Site Of Action Applications/pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, PAMAM G4-Paro 57 resulted in being more performant than bPEI, even in the presence of 10% and 50% in volume of fetal bovine serum (FBS). Afterward, we decided to also investigate the role of the PAMAM generation [ 73 ]. Accordingly, with the same synthetic strategy and a slightly different linker, we prepared four new conjugates starting from PAMAM dendrimers of different generations, namely PAMAM G2-Neo 59 , PAMAM G4-Neo 60 , and PAMAM G7-Neo 62 , bearing 13, 40, and 307 neomycin moieties, respectively ( Figure 17 b) [ 73 ].…”
Section: Polymeric Ag-based Gene Delivery Vectorsmentioning
confidence: 99%